THE RELATIONSHIP BETWEEN INNOVATIVE REGIONS AND SOCIAL CAPITAL IN TÜRKIYE - Fatma Betül Urhan (PEOPLE: International Journal of Social Sciences, 2025)
Social capital as a resource shaped by trust, cooperation, norms, and networks of social relations enhances the collective action capacity of individuals and communities. This study aims to analyze the causal relationship between social capital and innovation and to assess its potential implications for regional development strategies. To that end, Turkey’s NUTS-I regions were examined over the period 1995–2023 based on their innovation performance. Using the most recent data from 2023, the relationship between regional innovation performance and social capital index values was investigated via correlation analysis. Innovation performance was measured using R&D expenditures, utility model counts, and patent counts, all drawn from the Turkish Patent and Trademark Office and the Turkish Statistical Institute. The findings reveal moderate-to-strong, positive, and statistically significant correlations between social capital and innovation indicators. This suggests that social capital supports local innovation capacity through mechanisms such as knowledge sharing, trust formation, and a culture of collaboration. By addressing the concept of social capital within a spatial context and examining its interaction with innovation from a geographical perspective, this study seeks to make an original contribution to the literature.